The Empirical Examination of Firm Value Drivers Regarding the Global Financial Crisis - Kiss, Anita (International Journal of Engineering and Management Sciences, 2017)
The article focuses the corporate value creation and the most important value drivers. The first goal of the paper is to classify the most relevant value drivers, and their function of the firms’ value. Further objective of this study is to introduce the effects of the 2007-2008 global financial crisis. This article demonstrates the following. The first part presents the value chain and illustrates the primary and the support activities of the corporates. The second section briefly presents the 2007-2008 financial global economic crisis, introducing its causes, events and financial aspects. The third empirical part of the article analyses the database featuring data from 18 European countries, 10 sectors and 1553 firms in the period between 2004 and 2011. At the end, the fourth part contains conclusions. Based on the related literature reviewed and in the conducted empirical research it can be assessed that 2008 can be seen unambiguously as the year of the financial crisis. In this year, all predictors had a negative effect on the criterion variable, the firm value.